Rationally patterned electrode of direct-current triboelectric nanogenerators for ultrahigh effective surface charge density - Zhao, Zhihao; Dai, Yejing; Liu, Di; Zhou, Linglin; Li, Shaoxin; Wang, Zhong Lin; Wang, Jie (Nature communications, 2020)
As a new-era of energy harvesting technology, the enhancement of triboelectric charge density of triboelectric nanogenerator (TENG) is always crucial for its large-scale application on Internet of Things (IoTs) and artificial intelligence (AI). Here, a microstructure-designed direct-current TENG (MDC-TENG) with rationally patterned electrode structure is presented to enhance its effective surface charge density by increasing the efficiency of contact electrification. Thus, the MDC-TENG achieves a record high charge density of ~5.4 mC m −2 , which is over 2-fold the state-of-art of AC-TENGs and over 10-fold compared to previous DC-TENGs. The MDC-TENG realizes both the miniaturized device and high output performance. Meanwhile, its effective charge density can be further improved as the device size increases. Our work not only provides a miniaturization strategy of TENG for the application in IoTs and AI as energy supply or self-powered sensor, but also presents a paradigm shift for large-scale energy harvesting by TENGs. Low charge density is the bottleneck for the applications of triboelectric nanogenerator (TENG). Here, the authors demonstrate a microstructure-designed direct-current TENG with rationally patterned electrode structure to enhance its effective charge density to a new milestone.